2021
DOI: 10.15562/jdmfs.v6i2.1219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sidaguri and jatropha on tooth microhardness and tooth surface: An in vitro evaluation using CLSM

Abstract: Objective:The purpose of this study was to evaluate the effect of herbal alternatives, extract of sidaguri (sida rhombifolia) combine with extract of jatropha sap (jatropha curcas) application on microhardness and morphology of tooth surface. Material and Methods: Twelve upper first premolar teeth were used in this study, prepared to Class I box cavities, and were then allocated into 4 groups (n=3). Group 1-3 were treated groups, applied with combined extracts of a small dose (5 mg), medium dose (25 mg), and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Extract of root of sidaguri has been practiced in relieving toothache by drinking the boiled water of the extracts, while jatropha sap and melittin are applied directly to the ached teeth. These suggested the extracts do not harm the body [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Extract of root of sidaguri has been practiced in relieving toothache by drinking the boiled water of the extracts, while jatropha sap and melittin are applied directly to the ached teeth. These suggested the extracts do not harm the body [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Level of erosion, as well as dentin hardness, is related to pulp out dosage and duration of application. 9 This can be assumed that pulp out is able to penetrate through the pores formed.…”
Section: Original Researchmentioning
confidence: 99%
“…8 In previous in vitro study, a decreased of tooth hardness and erosion were reported which was in line with duration and dosage of Pulp-Out applied. 9 It is assumed that the extracts are able to penetrate through the porosity formed and causing cell death. In addition, toxicity test of various doses of Pulp-Out showed no adverse effects occurred following its application both systemically and locally (unpublished data).…”
Section: Introductionmentioning
confidence: 99%